Predictors of cancer screening behavior of the working population in China based on the information-motivation-behavioral skills model - Wang, Zezhou; Zhou, Changming; Zhang, Li; Shen, Jie; Mo, Miao; He, Yulian; Zheng, Ying (Frontiers in Public Health, 2023)
The cancer screening rate in the working population is very low in China.Information-motivation-behavioral skills (IMB) model has been applied to elucidate screening behavior for various chronic diseases but has not been investigated in analyzing cancer screening behavior. This study aimed to examine factors influencing cancer screening behavior and their linkages based on the IMB model.A cross-sectional study was conducted in Shanghai, China from August to October 2021. Data was obtained through an anonymous questionnaire. Predictive relationships between variables in the IMB model and cancer screening behavior were evaluated. Structural equation modeling (SEM) was constructed to demonstrate the utility of the IMB model.Among the 556 participants included in the analysis, 34.4% of participants had ever done a cancer screening. The construct validation analysis supported that the measure items included were acceptable. SEM found that knowledge of cancer warning signs and symptoms (β = 0.563, P < 0.001) and cancer screening behavioral skills (β = 0.264, P = 0.003) were related to participation in cancer screening, whereas cancer screening motivation was not directly influenced the participation in cancer screening (β = − 0.075, P = 0.372).The cancer screening rate was found to be lower than expected in the working population. The IMB model could be used to make decisions in implementing behavioral interventions to participate in cancer screening among the Chinese working population. Enhancing the knowledge of cancer warning signs and symptoms and strengthening behavioral skills should be focused on to improve participation in cancer screening.